Social Representations of Overweight and Obesity in Schoolchild in the State of Mexico - Verónica Arreola Ríos; Donovan Casas Patiño (Revista Finlay)
Foundation: overweight and obesity in school constitute a Public Health problem in Mexico and the world. Childhood obesity is one of the main health problems of the 21st century. Objective: to compare the social construction of overweight and obesity in primary school students in the State of Eastern Mexico through the theory of social representations. Method: a qualitative study was carried out in which 5 public education institutions dependent on the Secretary of Public Education of the Municipality of Amecameca, Atlautla and Ozumba at the primary level from 6 to 12 years old were analyzed. The convenience study sample was 52 children. In this study, social representations were addressed in order to understand and compare the social construction of overweight and obesity in primary school students in the State of Eastern Mexico. Results: the diet is focused on what schoolchildren can eat and what their primary caregivers who determine the diet can buy; a very high degree of stigmatization is shown at the school and social level, there is a decrease in certain consumption of foods - high in calories and fashionable -, it conditions emotional sensations such as: sadness, anger and fear, physical activity is found during school breaks, which brings them happiness and by not achieving this at home, causes them discomfort. Conclusions: primary caregivers are those who determine the diet; there was a very high degree of stigmatization at the school and social level; there is a decrease in certain consumption of high-calorie foods; physical activity occurs almost exclusively during school breaks.